Scaling peak VO2 to body mass in young male and female distance runners - Eisenmann, J. C.; Pivarnik, J. M.; Malina, R. M. (Journal of Applied Physiology, 2001)
This study examined age- and sex-associated variation in peak oxygen consumption (VO2) of young male and female distance runners from an allometric scaling perspective. Subjects were from two separate studies of 9- to 19-yr-old distance runners from the mid-Michigan area, one conducted between 1982 and 1986 (Young Runners Study I, YRS I) and the other in 1999-2000 (Young Runners Study II, YRS II). Data from 27 boys and 27 girls from YRS I and 48 boys and 22 girls from the YRS II were included, and a total of 139 and 108 measurements of body size and peak VO2 in boys and girls, respectively, were available. Subjects were divided into whole year age groups. A 2 × 9 (sex × age group) ANOVA was used to examine differences in peak VO2. Intraindividual ontogenetic allometric scaling was determined in 20 boys and 17 girls measured annually for 3-5 yr. Allometric scaling factors were calculated using linear regression of log-transformed data. Results indicated that 1) absolute peak VO2 increases with age in boys and girls, 2) relative peak VO2 (ml · kg1 · min1) remains relatively stable in boys and in girls, 3) relative peak VO2 (ml · kg0.75 · min1) increases throughout the age range in boys and increases in girls until age 15 yr, and 4) peak VO2 adjusted for body mass (ml/min) increases with age in boys and girls. The overall mean cross-sectional scaling factor was 1.01 ± 0.03 (SE) in boys and 0.85 ± 0.05 (SE) in girls. Significant age × sex interactions and significant scaling factors between sexes identify the progressive divergence of peak VO2 between adolescent male and female distance runners. Mean ontogenetic allometric scaling factors were 0.81 [0.71-0.92, 95% confidence interval (CI)] and 0.61 (0.50-0.72, 95% CI) in boys and girls, respectively (P = 0.002). There was considerable variation in individual scaling factors (0.51-1.31 and 0.28-0.90 in boys and girls, respectively). The results suggest that the interpretation of growth-related changes in peak VO2 of young distance runners is dependent upon the manner of expressing peak VO2 relative to body size and/or the statistical technique employed.